Agricultural residues as substrates in the production of formosa papaya, okra and zucchini seedlings - Paola Lo Monaco; Larissa Ionara Silva Paula; Paola Honorato Salla; Ismail Ramalho Haddade; Gustavo Haddad Souza Vieira; Rodrigo Junior Nandorf; Lillya Mattedi (Bioscience Journal, 2020)
Using residues generated in agriculture to produce seedlingsis an economically interesting alternative, besides being a way to reduce the environmental impacts caused by their inadequate disposal. This study aimed to evaluate the potential of using coffee chaff (CC) and organic compost (OC) as substrate components for the production of Formosa papaya seedlings and the potential of grape pomace (GP), a vitiviniculture residue, in the composition of substrates for the production of okra and zucchini seedlings. We carried out two trials in a completely randomized design (CRD): the first had seven treatments and six replicates: T0: 100% commercial substrate Bioplant® (CS); from T1 to T6: increasing proportions of CC and decreasing of CC: 10/90; 20/80; 30/70; 40/60; 50/50 e 60/40%. The second had six treatments and six replicates, with increasing proportions of GP and decreasing proportions of CS: 0/100; 10/90; 20/80; 30/70; 40/60 and 50/50%.In the first trial we evaluated the number of leaves, root length, seedling height, stem diameter, shoot dry mass, root dry mass, total dry mass and Dickson Quality Index (DQI) at 59 days after sowing.The second trialwas performed at 12 and 18 DAS and we analyzed the number of leaves, plant height, root length, collar diameter, shoot dry mass, root dry mass, total dry mass and Dickson Quality Index (DQI). Variables that met the assumptions of normality and homoscedasticity were subjected to Dunnett’s test. The substrate composed of coffee chaff and organic compost has a high potential to be used as an alternative substrate due to promote better quality of papaya seedlings compared to the commercial substrate. Alternative substrate containing 60% coffee chaff and 40% organic compost is recommended for the production of  Formosa papaya seedlings in tubes. The grape pomace (GP) has a high potential to be used as component in substrate for the production of okra and zucchini seedlings compared to the commercial substrate (CS) only. Alternative substrate composed of 50% GP and 50% CS is recommended for the production of zucchini seedlings, while substrate composed of 10% GP and 90% CS is recommended for the production of okra seedlings.